One-Pot Synthesis of Triazolo-Heterolignans: Biological Evaluation and Molecular Docking Studies as Tubulin Inhibitors - Reddy, Chada R.; Subbarao, Muppidi; Vijaykumar, Jonnalagadda; Jadav, Surender Singh; Sasane, Nilesh; Valleti, Reddi Rani; Supriya, Bhukya; Ummanni, Ramesh (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: The anti-mitotic activity of podophyllotoxin derivative targeting tubulin enzyme proved them as strong polymerization inhibitors. The introduction of heteroatom along with different heteroaryl systems in naturally obtained lignans created a latitude for design of bioactive components. A novel one-pot sequential propargylation/cycloaddition reaction strategy has been followed to synthesize triazolo-heterolignans. Objective: To screen anti-proliferative activity of novel heterolignans and to determine their mode of action. Method: SRB assay, Cytotoxicity evaluation, PI uptake for analysis of cell cycle, caspase-3 activity, Western blot analysis and Immunofluorescence and molecular docking studies. Results: SRB assay of synthesised compounds were provided compound 3a and 5f to be highly active among the synthesized compounds. The Compound 3a showed cell cycle arrest at G2/M phase and 5f arrest the cells at G1 phase. Compound 5f displayed caspase 3 mediated apoptotic effect at lower levels. Compound 3a and 5f displayed microtubule disassembly inhibition same as paclitaxel and found to be occupying colchicine binding site of tubulin, both ligands were depicted π-cation interaction with Lys352 residue and triazole ring accommodated at the lactone binding site. Conclusion: A novel one-pot sequential propargylation/cycloaddition reaction has been developed for the synthesis of triazolo-heterolignans. Compound 3a and 5f were displayed good cytotoxic activities and found to inhibit microtubule disassembly. The importance of triazole ring of heterolignans has been studied by molecular docking experiments and results were compared.
Keywords: Heterolignan